2018
DOI: 10.1371/journal.pone.0195247
|View full text |Cite
|
Sign up to set email alerts
|

Weather and landscape factors affect white-tailed deer neonate survival at ecologically important life stages in the Northern Great Plains

Abstract: Offspring survival is generally more variable than adult survival and may limit population growth. Although white-tailed deer neonate survival has been intensively investigated, recent work has emphasized how specific cover types influence neonate survival at local scales (single study area). These localized investigations have often led to inconsistences within the literature. Developing specific hypotheses describing the relationships among environmental, habitat, and landscape factors influencing white-tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 60 publications
(91 reference statements)
0
28
3
Order By: Relevance
“…The high availability of these crops, combined with a relatively low deer density during the study (~7 deer/km 2 ; K. H. Wiskirchen, Missouri Department of Conservation, personal communication), and similar birth masses to comparable regions (2.56–2.81 kg in South Dakota, USA [Grovenburg et al ], 2.47–4.16 kg in northern Michigan, USA [Duquette et al ]) makes it unlikely that neonate survival was low in the GP because of nutritional constraints. Unfavorable spring and summer weather conditions can also lead to a decline in neonate survival rates (Gilbert and Raedeke , Warbington et al , Michel et al ); however, we did not observe abnormally cold or wet weather during our study. Further, we did not observe higher incidences of natural‐caused mortality, such as disease or abandonment.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…The high availability of these crops, combined with a relatively low deer density during the study (~7 deer/km 2 ; K. H. Wiskirchen, Missouri Department of Conservation, personal communication), and similar birth masses to comparable regions (2.56–2.81 kg in South Dakota, USA [Grovenburg et al ], 2.47–4.16 kg in northern Michigan, USA [Duquette et al ]) makes it unlikely that neonate survival was low in the GP because of nutritional constraints. Unfavorable spring and summer weather conditions can also lead to a decline in neonate survival rates (Gilbert and Raedeke , Warbington et al , Michel et al ); however, we did not observe abnormally cold or wet weather during our study. Further, we did not observe higher incidences of natural‐caused mortality, such as disease or abandonment.…”
Section: Discussioncontrasting
confidence: 68%
“…In South Dakota, as in the GP, forests are likely functionally different for neonates than in forest‐dominated systems (i.e., no longer considered cover habitat) because the patches of forest are small and highly fragmented. Michel et al () found that in the Great Plains region, neonate survival was largely influenced by patch connectivity, further emphasizing the importance of landscape configuration and proximity to cover in fragmented systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to winter climate, spring and autumn weather may also be important for deer populations. Colder temperatures and presence of rainfall in spring have been reported to decrease young fawn survival in some areas, although increased precipitation has been correlated with increased survival (Ginnett and Young , Warbington et al , Michel et al ). Additionally, warmer and wetter weather in spring and autumn have been reported to positively influence deer reproduction, whereas snow in autumn negatively affected survival, possibly because it reduced forage availability at a critical time (Simard et al ).…”
Section: Resultsmentioning
confidence: 99%